Draft Annual Plan 2004-05 Haryana State - Planning Commission (Planning Commission, 2004)
State Government had proposed an outlay of Rs. 2100 crore for Annual Plan 2003- 04 to Planning Commission, Government of India. However, Planning Commission has approved the State’s core Annual Plan 2003-04 for Rs. 2068.00 crore. Later on, Planning Commission sanctioned Additional Central Assistance of Rs. 23.00 crore to Haryana State. Consequently, the State’s Approved Outlay for Annual Plan 2003-04 is enhanced to Rs. 2091.00 crore.
Planning Department Government of Haryana